Comparative analysis of the complete chloroplast genomes of six threatened subgenus Gynopodium (Magnolia) species - Xie, Huanhuan; Zhang, Lei; Zhang, Cheng; Chang, Hong; Xi, Zhenxiang; Xu, Xiaoting (BMC genomics, 2022)
The subgenus Gynopodium belonging to genus Magnolia have high ornamental, economic, and ecological value. Subgenus Gynopodium contains eight species, but six of these species are threatened. No studies to date have characterized the characteristics of the chloroplast genomes (CPGs) within subgenus Gynopodium species. In this study, we compared the structure of CPGs, identified the mutational hotspots and resolved the phylogenetic relationship of subgenus Gynopodium. The CPGs of six subgenus Gynopodium species ranged in size from 160,027 bp to 160,114 bp. A total of 131 genes were identified, including 86 protein-coding genes, eight ribosomal RNA genes, and 37 transfer RNA genes. We detected neither major expansions or contractions in the inverted repeat region, nor rearrangements or insertions in the CPGs of six subgenus Gynopodium species. A total of 300 large repeat sequences (forward, reverse, and palindrome repeats), 847 simple sequence repeats, and five highly variable regions were identified. One gene (ycf1) and four intergenic regions (psbA-trnH-GUG, petA-psbJ, rpl32-trnL-UAG, and ccsA-ndhD) were identified as mutational hotspots by their high nucleotide diversity (Pi) values ([greater than or equal to] 0.004), which were useful for species discrimination. Maximum likelihood and Bayesian inference trees were concordant and indicated that Magnoliaceae consisted of two genera Liriodendron and Magnolia. Six species of subgenus Gynopodium clustered as a monophyletic clade, forming a sister clade with subgenus Yulania (BS = 100%, PP = 1.00). Due to the non-monophyly of subgenus Magnolia, subgenus Gynopodium should be treated as a section of Magnolia. Within section Gynopodium, M. sinica diverged first (posterior probability = 1, bootstrap = 100), followed by M. nitida, M. kachirachirai and M. lotungensis. M. omeiensis was sister to M. yunnanensis (posterior probability = 0.97, bootstrap = 50). The CPGs and characteristics information provided by our study could be useful in species identification, conservation genetics and resolving phylogenetic relationships of Magnoliaceae species.